2016
DOI: 10.3144/expresspolymlett.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of macrogel composition from industrial natural rubber samples: Influence of proteins on the macrogel crosslink density

Abstract: Abstract. The insoluble (macrogel) and soluble fractions of 11 commercial natural rubber (NR) samples (Technically specified rubber) were separated. Nitrogen titrations and lipid extractions enabled a quantitative assessment of the proteins and extractable lipids in each fraction. Swelling was measured in tetrahydrofuran in order to evaluate the crosslink density (M c -1 ) of each macrogel. While the soluble fraction had a high lipid concentration, the majority of non-isoprene compounds of the macrogel were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This is in agreement with the correlation between the protein content and the gel content [49], which suggested that proteins were involved in the majority of crosslinks in NR [45,50]. Furthermore, these proteins were also suggested to be involved in the structuring of microaggregates, also called as "microgel" [44]. Of course, we cannot rule out completely the PMMA graft polymer may also lead to the restriction of the large-scale relaxation of NR-g-PMMA.…”
Section: Rheological Properties Of the Parent Polymerssupporting
confidence: 83%
See 1 more Smart Citation
“…This is in agreement with the correlation between the protein content and the gel content [49], which suggested that proteins were involved in the majority of crosslinks in NR [45,50]. Furthermore, these proteins were also suggested to be involved in the structuring of microaggregates, also called as "microgel" [44]. Of course, we cannot rule out completely the PMMA graft polymer may also lead to the restriction of the large-scale relaxation of NR-g-PMMA.…”
Section: Rheological Properties Of the Parent Polymerssupporting
confidence: 83%
“…This behavior may be attributed to the network of crosslinked chains (e.g., microgels), which restricted the long-range motion of chains. Works have been reported that the extracted NR contained nitrogen-containing compounds even after extensive purification [43,44]. These nitrogeneous compounds, namely proteins and phospholipids, formed an intermolecular interaction at the NR chain ends via hydrogen bonding, which possibly formed branching and gels [43,45,46], as a naturally occurring network [47,48].…”
Section: Rheological Properties Of the Parent Polymersmentioning
confidence: 99%
“…Another probable cause of variations is that drying and chewing are not rigorously controlled in small plantations. It has been reported that molecular weight and gel content in NR vary markedly with the drying conditions after washing with water, because storage hardening takes place after drying even if the natural rubber is left to stand at room temperature [10].…”
Section: Properties Of Nr Sheets-based Compoundsmentioning
confidence: 99%
“…These yields to variability in NR properties, what generates loss of materials and energy during the various stages of industrial processes [10]. Variations can be explained because NR latex is a very complex colloidal system.…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that NR and deproteinised NR could not proceed with storage hardening after lipid/phospholipid groups linked to NR molecules were decomposed by transesterification reaction while the role of proteins in storage hardening is negligible [8]. On the contrary, the macrogel of various commercial grades of NR samples after at least 14 months of storage was found to contain a high content of nitrogen [15]. It was proposed that proteins are involved in the majority of crosslinks in macrogel.…”
Section: Introductionmentioning
confidence: 99%